THE INFLUENCE OF SERVICE QUALITY AND PROMOTION ON CONSUMER PURCHASING DECISIONS - Putri Nilam Kencana; Baliyah Munadjat; Windy Gustia Wardani (International Journal Management and Economic, 2024)
This research aims to investigate the impact of Service Quality and Promotion on Consumer Purchasing Decisions at Mister Donut PIK Avenue Mall Jakarta, both partially and simultaneously. The method used was quantitative, with a random sampling technique involving 100 respondents. Data analysis was carried out through multiple regression analysis. The research results show that Service Quality has a significant influence on Purchasing Decisions, and promotion also has a significant influence on Purchasing Decisions. Simultaneously, Service Quality and Promotion significantly influence Purchasing Decisions with the regression equation Y = 6.974 + 0.344 X1 + 0.500 X2. The correlation coefficient shows a strong relationship, with a determination value of 81.8%, indicating the contribution of the influence of this variable, while other factors influence 18.2%.